The behaviour of foals before and after weaning in group - Muhonen, Sara; Lönn, Maria (SLU/Dept. of Animal Nutrition and Management (until 231231), 2003)
Weaning is a standard procedure at most studs, and the methods of weaning varies greatly. The method used at the stud in this particular study is supposed to decrease stress. The purpose of the study was to compare the behaviour of foals in group before and after stepwise removal of their mares.